Decrease in pregnancy rate after endometrial scratch in women undergoing a first or second in vitro fertilization. A multicenter randomized controlled trial. Issue 1 (29th November 2018) - Frantz, Sandrine; Parinaud, Jean; Kret, Marion; Rocher-Escriva, Gaelle; Papaxanthos-Roche, Aline; Creux, Hélène; Chansel-Debordeaux, Lucie; Bénard, Antoine; Hocké, Claude
Abstract: STUDY QUESTION: Does endometrial scratch in women undergoing a first or second IVF/ICSI attempt improve the clinical pregnancy rate (CPR)? SUMMARY ANSWER: Endometrial scratch (ES) in women undergoing their first or second IVF/ICSI attempt does not enhance the CPR under the technical conditions of our study. WHAT IS KNOWN ALREADY: Several studies have suggested that physical scratch of the endometrium before an IVF attempt could improve embryo implantation. STUDY DESIGN, SIZE, DURATION: This was a randomized controlled multi-center, two-arm, parallel trial. Inclusions started in February 2010 and stopped prematurely in July 2014 after an unplanned interim analysis. At the time of study closure, 191 of the planned 358 patients had been included. PARTICIPANTS/MATERIALS, SETTING, METHODS: Patients included in the study were randomly assigned to either the ES arm or the non-ES arm. Local ES was performed between Day 20 and Day 24 of the cycle preceding ovarian stimulation using a device for endometrial biopsy. Ovarian stimulation used a combination of recombinant FSH and either an GnRH agonist protocol or a GnRH antagonist protocol without any estrogen pre-treatment. CPR was analyzed on an intent-to-treat basis. All comparisons between the two groups were done using a logistic regression model adjusted for age, BMI and infertility etiology. Differences between the two arms were considered statistically significant at P value of less than 0.0446 for the primary outcome only. MAIN RESULTS AND THE ROLE OF CHANCE: Sixty-eight embryo transfers were performed in the ES arm and sixty-four in the non-ES arm. CPR was 23.5% (16/68) in the ES arm and 35.9% (23/64) in the non-ES arm (hazard ratio (HR) = 0.43; 95% CI, 0.18–1.02; P = 0.0568). The implantation rate was 19.1% and 24.0% in the ES arm and in the non-ES arm, respectively. Two miscarriages and one ectopic pregnancy were reported in each arm. The multiple pregnancy rate was higher in the scratch arm (50.0% vs 20.0%), but the difference was not statistically significant (odds ratio (OR) = 4.54; 95% CI, 0.50–40.93; P = 0.1349). The endometrial biopsy procedure was well tolerated in most women. Of 50 patients in the ES arm having received the embryo transfer, 40 (80.0%) patients reported having felt pain during the procedure, the pain resolving quickly for 31 of them. LIMITATIONS, REASONS FOR CAUTION: An interim analysis of the primary endpoint was conducted and an independent data monitoring committee agreed on stopping the inclusions. This analysis was prompted by the tendency towards lower pregnancy rates observed in the ES arm. Consequently, the study suffered from a lower inclusion rate and failed to reach the planned sample size. WIDER IMPLICATIONS OF THE FINDINGS: Under the technical condition employed in this study, ES in the luteal phase of the cycle preceding the ovarian stimulation does not improve CPR in patients undergoing a first or second IVF/ICSI attempt. STUDY FUNDING/COMPETING INTERESTS: This study was supported by a grant from Ministère de la Santé Français (Programme Hospitalier de Recherche Clinique 2009). There are no conflicts of interest. TRIAL REGISTRATION NUMBER: NCT01064193 TRIAL REGISTRATION DATE: 08-Feb-2010 DATE OF FIRST PATIENT'S ENROLMENT: 08-Feb-2010